Effect of chemical activators after intracytoplasmic sperm injection (ICSI) on embryo development in alpacas - Bellido Quispe, Dionet Keny (2024)
Low motility and low sperm concentration are characteristics of alpaca semen. Thus, the intracytoplasmic sperm injection (ICSI) technique represents an alternative to improve the reproductive capacity of the male. However, the effect of post-ICSI activation in alpaca is not yet known. The aim of the present study was to compare the effect of chemical activators on alpaca embryo development after ICSI. Alpaca ovaries were collected from a local slaughterhouse and transported to the laboratory. Category I, II and III oocytes were matured for 30 h at 38.5 °C. After ICSI, injected oocytes were randomly divided and activated as follows: i) 5 μM ionomycin for 5 min, ii) 7% ethanol for 4 min, iii) 5 μM ionomycin for 5 min, window period 3 h plus 7% ethanol for 4 min, iv) 5 μM ionomycin for 5 min, window period 3 h, a second ionomycin treatment for 5 min, followed by 1.9 mM 6-DMAP for 3 h, v) 10 mM SrCl2 for 3 h. Culture was carried out for 5 days in SOFaa at 38.5 °C. The cleavage rate was the lowest in the SrCl2 group, morula development was the lowest in the SrCl2 and without activation groups, and blastocyst stage was not different between groups (P<0.05). The rates with SrCl2 were lower in total embryos produced, whereas in transferable embryos they were lower with 2Io/6-DMAP and with SrCl2 (P<0.05). In conclusion, alpaca oocyte activation is more efficient with ionomycin and ethanol to produce transferable embryos.